An Intronic cis-Regulatory Element Is Crucial for the Alpha Tubulin Pl-Tuba1a Gene Activation in the Ciliary Band and Animal Pole Neurogenic Domains during Sea Urchin Development. - Salvatore Costa; Aldo Nicosia; Angela Cuttitta; Fabrizio Gianguzza; Maria Antonietta Ragusa (PLoS ONE)
In sea urchin development, structures derived from neurogenic territory control the swimming and feeding responses of the pluteus as well as the process of metamorphosis. We have previously isolated an alpha tubulin family member of Paracentrotus lividus (Pl-Tuba1a, formerly known as Pl-Talpha2) that is specifically expressed in the ciliary band and animal pole neurogenic domains of the sea urchin embryo. In order to identify cis-regulatory elements controlling its spatio-temporal expression, we conducted gene transfer experiments, transgene deletions and site specific mutagenesis. Thus, a genomic region of about 2.6 Kb of Pl-Tuba1a, containing four Interspecifically Conserved Regions (ICRs), was identified as responsible for proper gene expression. An enhancer role was ascribed to ICR1 and ICR2, while ICR3 exerted a pivotal role in basal expression, restricting Tuba1a expression to the proper territories of the embryo. Additionally, the mutation of the forkhead box consensus sequence binding site in ICR3 prevented Pl-Tuba1a expression.